Toward a History of the Blind in Spain - Madeline Sutherland-Meier (Disability Studies Quarterly, 2015)
This paper uses archival documents, literature, and art to sketch the history of the blind in Spain. Traditionally, certain occupations, such as singing and playing musical instruments, saying prayers and selling chapbooks were reserved for the blind. Spanish artists and writers have portrayed the blind engaged in these occupations. Starting in the Middle Ages, the blind established powerful brotherhoods through which they controlled these professions. The changing roles that the blind played in the creation, production, performance and sale of popular literature known as literatura de cordel show their successful adaptation to an emerging print culture. The situation of the blind today and the success of the National Organization of the Spanish Blind (ONCE) are also discussed.
Keywords: blind; history of disability; Spain; literatura de cordel; romance de ciego; hermandades; cofradías; reserved occupations; ONCE